2012
DOI: 10.1212/wnl.0b013e3182452b40
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation at CR1 increases risk of cerebral amyloid angiopathy

Abstract: Objective: Accumulated evidence suggests that a variant within the CR1 gene (single nucleotide polymorphism rs6656401), known to increase risk for Alzheimer disease (AD), influences ␤-amyloid (A␤) deposition in brain tissue. Given the biologic overlap between AD and cerebral amyloid angiopathy (CAA), a leading cause of intracerebral hemorrhage (ICH) in elderly individuals, we investigated whether rs6656401 increases the risk of CAA-related ICH and influences vascular A␤ deposition. Methods:We performed a case-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
79
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 32 publications
2
79
0
Order By: Relevance
“…The associations between the two genes and AD have been identified and replicated by a number of independent studies [see e.g., Harold et al, 2009; Hollingworth et al, 2011; Lambert et al, 2009; Naj et al, 2011], in addition to Lambert et al [2013], and their potential contributions to the mechanism of AD have been under active investigation [Biffi et al, 2012; Chibnik et al, 2011; Thambisetty et al, 2013]. Moreover, recent studies show that many of the AD risk genes have potential roles in relationship with CVD risk factors, such as hypertension, hypercholesterolemia, and obesity [Guerreiro et al, 2012; Liu et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…The associations between the two genes and AD have been identified and replicated by a number of independent studies [see e.g., Harold et al, 2009; Hollingworth et al, 2011; Lambert et al, 2009; Naj et al, 2011], in addition to Lambert et al [2013], and their potential contributions to the mechanism of AD have been under active investigation [Biffi et al, 2012; Chibnik et al, 2011; Thambisetty et al, 2013]. Moreover, recent studies show that many of the AD risk genes have potential roles in relationship with CVD risk factors, such as hypertension, hypercholesterolemia, and obesity [Guerreiro et al, 2012; Liu et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…4,11,12 Particiapnts were selected among consecutive patients age ≥ 18 years, admitted to Massachusetts General Hospital (MGH) from January 2006 to December 2013 with primary ICH, i.e. not related to trauma, conversion of an ischemic infarct, rupture of a vascular malformation / aneurysm, or a brain tumor (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have also reported low expression of CR1 in some brain regions (Chibnik et al 2011; Bralten et al 2011), and CR1 interacted with APOE and participated in the clearance of β amyloid (Aβ) peptide. Aβ is the principal constituent of amyloid plaques that is one of the major brain lesions of individuals with AD (Thambisetty et al 2013; Lambert et al 2009; Biffi et al 2012). …”
Section: Discussionmentioning
confidence: 99%